2009
DOI: 10.1007/s12190-008-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal pattern formation in a diffusive predator-prey system: an analytical approach

Abstract: In this paper, we propose and analyse a mathematical model to study the mathematical aspect of reaction diffusion pattern formation mechanism in a predatorprey system. An attempt is made to provide an analytical explanation for understanding plankton patchiness in a minimal model of aquatic ecosystem consisting of phytoplankton, zooplankton, fish and nutrient. The reaction diffusion model system exhibits spatiotemporal chaos causing plankton patchiness in marine system. Our analytical findings, supported by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Hillary and Bees [3] compared the dynamics of the plankton communities with and without the delay associated with a zooplankton maturation period and found that time delay can lead to progressively replacing regular plankton dynamics by chaos. There are also other causes of delays in population dynamics at various time scales [5,7,[11][12][13][14]18]. Consequently, delay needs to be considered.…”
Section: Zooplankton Fishmentioning
confidence: 99%
See 4 more Smart Citations
“…Hillary and Bees [3] compared the dynamics of the plankton communities with and without the delay associated with a zooplankton maturation period and found that time delay can lead to progressively replacing regular plankton dynamics by chaos. There are also other causes of delays in population dynamics at various time scales [5,7,[11][12][13][14]18]. Consequently, delay needs to be considered.…”
Section: Zooplankton Fishmentioning
confidence: 99%
“…Furthermore, we have noted that the ecological system is often deeply perturbed by human exploiting activities over recent years [5,19,20]. For the view of human needs, the exploitation of ecological resources and harvest of population are commonly carried out in the fields of wildlife, fishery and forestry management [14]. As a consequence, people are facing the problems about shortage of resource and worsening environment.…”
Section: Zooplankton Fishmentioning
confidence: 99%
See 3 more Smart Citations